Driving Transforming E-Governance: the Innovation Nexus from Indonesia and Vietnam - Likuwatan Werang, Nicolaus Petrus; Lusiana Florentin Werang, Maria; Han, Bao (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
Driving transformation for e-governance becomes a role to play in assisting the government’s public-sector initiative. The reason for this is that e-governance must be inclusive. Our reason for this attempt is to examine the nexus of innovation that Indonesia and Vietnam have actualized. Both countries have advanced digital infrastructure in recent years, yet progress in human capital development, especially digital skills, has not kept pace. Based on this, we explore e-governance through public-private sector engagement, stress the growing gap between technological progress and citizens’ digital skills, and examine trends in digital infrastructure development, using secondary data from published surveys. The findings note that e-governance has made great strides, but human capital development is still lagging, with slower growth in digital skills. The implications of this essay underline the critical role of entities’ engagement in advancing e-governance and call for greater investment in digital literacy to enable all citizens to recognize the essence of digital transformation and ensure inclusive and sustainable progress.